International politics concepts, theories and issues - Basu, Rumki (Sage Publications, 2012)
The study of international politics has become truly global in nature and scope, as the world stands politically organised in nearly two hundred nation states at the beginning of the second decade of the 21st century. This book provides a roadmap that can orient the reader towards the main concepts, theories and issues in world politics.